2006
DOI: 10.1089/dis.2006.9.201
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation Management: A New Approach

Abstract: Anticoagulation therapy has been identified as an area in which new approaches to treatment and monitoring may allow for significant improvements in healthcare quality and costs. We evaluated the potential benefits of a new approach to anticoagulation therapy, utilizing decision support software, point-of-service testing, and workflow redesign. We performed an intervention study in the setting of a university-affiliated primary care clinic, involving 40 patients receiving chronic anticoagulation therapy. Study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…The patient is contacted, usually by writing and in some cases by phone, and is given the instructions for drug intake and next date of measurement. 1 This is traditionally managed in a paper record system.…”
Section: Introductionmentioning
confidence: 99%
“…The patient is contacted, usually by writing and in some cases by phone, and is given the instructions for drug intake and next date of measurement. 1 This is traditionally managed in a paper record system.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of one INR test in 2006 ranged from US$6.19 of revenue for point‐of‐care testing (POCT) in a primary care clinic (Wurster & Doran, 2006) to $145.70 for a home visit plus laboratory test (Björholt et al. , 2007) (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…44 Four of the RCTs investigated PoCT with another intervention. 8,18,21,34,58,59 The geographical setting included the United Kingdom (n=13) 8,16,18,21,33,[60][61][62][63][64][65][66][67] , Australia (n=7) 17,23,47,[68][69][70][71] , USA (n=5) 44,58,[72][73][74] , Belgium (n=2) 34,59 , Sweden (n=1) 75 and Ireland (n=1). 76 A description of the 29 studies included in the review is reported in Table 13 and Table 14.…”
Section: Excluded Studiesmentioning
confidence: 99%
“…Three undertook a cost-effectiveness analysis (two from a health care provider perspective 21,59 and one from a patient perspective 67 ); two reported the practice costs incurred 64,73 and one study 62 reported costs of the device and test. Claes et al 59 found that PoCT provided net savings for the health care provider while Parry et al 21 found PoCT costs to be greater than usual care to the health care provider.…”
Section: Inr Poctmentioning
confidence: 99%
See 1 more Smart Citation